Theoretical and experimental investigations on high peak power Q-switched Nd:YAG laser at 1112 nm. (July 2018) - He, Miao; Yang, Feng; Wang, Zhi-Chao; Gao, Hong-Wei; Yuan, Lei; Li, Chen-Long; Zong, Nan; Shen, Yu; Bo, Yong; Peng, Qin-Jun; Cui, Da-Fu; Xu, Zu-Yan
Highlights: Single wavelength of 1112 nm is realized by precise coating on cavity mirrors. We report the highest pulse energy and peak power of a laser operating at 1112 nm. We report a good seeder for power scaling and high efficiency frequency conversion. Time delay of the Q-switch should be carefully optimized. Abstract: We report on the experimental measurement and theoretical analysis on a Q-switched high peak power laser diode (LD) side-pumped 1112 nm Nd:YAG laser by means of special mirrors coating design in cavity. In theory, a numerical model, based on four-wavelength rate equations, is performed to analyze the competition process of different gain lines and the output characteristics of the Q-switched Nd:YAG laser. In the experiment, a maximum output power of 25.2 W with beam quality factor M 2 of 1.46 is obtained at the pulse repetition rate of 2 kHz and 210 ns of pulse width, corresponding to a pulse energy and peak power of 12.6 mJ and 60 kW, respectively. The experimental data agree well with the theoretical simulation results.